Directivity based nanoscopic position sensing - Bag, Ankan; Neugebauer, Martin; Wozniak, Pawel; Leuchs, Gerd; Banzer, Peter (Springer Verlag, 2017)
Precise position sensing of a nanoparticle or a biomolecule is of paramount importance for the field of photonics, specifically in medicine and biophysics. This is a fundamental step towards several super-resolution imaging techniques, such as fluorescence based photoactivated localization microscopy (PALM) [1]. In the last decade, using different nonlinear or linear techniques, a localization precision down to few nanometers, even Ångström has been achieved [2]. Here, we present a new concept of position sensing enabling Ångström accuracy, based on strongly directional light emission off a single subwavelength dielectric scatterer. To realize the strong directional emission, we take advantage of a high refractive index dielectric silicon nanosphere, which supports both electric as well as magnetic resonances in the visible spectra [3]. As a probe beam, we use a radially polarized vector beam, which upon tight focusing provides an inhomogeneous field distribution, with a strong longitudinal electric field component present on-axis [4]. While, the transverse electric field components vanish on-axis, but increase linearly with radial distance (linearity holds in close vicinity to optical axis, around 50 nm). Using this tailored electromagnetic field, electric and magnetic dipoles resonances can be induced in the dielectric scatterer, when it is located off-axis; and interference of those dipole emissions may yield strong directional emission (see Fig. 44.1). By appropriately choosing the wavelength of the probe beam, this directivity has been maximized to get a strong position dependence. With proper calibration of this strong position dependent directivity, it was possible to show that a displacement of 5 nm can be easily distinguished whereas with further statistical analysis, it was possible to resolve smaller displacement with position uncertainty of 0:2 nm. This fast, easy to calibrate, linear technique can be very much useful for high resolution spatial and temporal particle localization and several other applications, also might constitute an alternative pathway towards linear high resolution imaging.
CRIS-Team Scopus Importer:2023-04-20